UPAYA PEMERINTAH DAERAH DALAM PENGEMBANGAN INFRASTRUKTUR OLAHRAGA (STUDI KASUS KAWASAN SPORT CENTRE KABUPATEN POLEWALI MANDAR) - Abd. Asis (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2017)
This study aims to determine the efforts of local governments in the development of sports infrastructure and management of the Sport Center in the management of sports infrastructure at the H.S Stadium. Holding, Sport and Tennis Court H.S. Mengga. Research shows that local governments carry out infrastructure development in accordance with the government's annual activity program and also the Regent's policy from 2015 to 2017. There is always an increase and development in the area sport center. In addition, the UPTD Sport Center as the organizer of the sports infrastructure management plan at the HS Mengga Stadium and the HS Mengga GOR is quite good, on the Tennis Court it is still not good, organizing at the HS Mengga Stadium, HS Mengga GOR and Tennis Court are considered good. The implementation at the HS Mengga Stadium, the HS Mengga Tennis Court was grouped in good categories. Supervision at HS Mengga Stadium and GOR HS Mengga is good but on the Tennis Court it is still not good.